Clinical Benefits of Parasternal Block with Multihole Catheters when Inserted before Sternotomy - Vedat Eljezi; Crispin Jallas; Bruno Pereira; Melanie Chasteloux; Christian Dualé; Lionel Camilleri (Annals of Cardiac Anaesthesia)
Background: The aim of this study was to assess whether parasternal block with multihole catheters inserted before surgical incision enables to alleviate postoperative analgesia and opioid reduction in cardiac surgery patients with sternotomy. Methods: Twenty-six adult patients scheduled for cardiac surgery with sternotomy aged between 18 and 84 olds were included in this prospective, monocentric, open, single-group trial. Two parasternal multihole catheters were inserted on each side of the sternum before the surgical skin incision for cardiac surgery and 10 mL of ropivacaine 7.5 mg mL–1 was initially administered in each catheter. Local anesthetic administration followed by continued infusion at 3 mL hr–1 of ropivacaine 2 mg mL–1 per catheter for 48 h postoperatively upon patient arrival in the intensive care unit. The efficacy of the parasternal block was assessed according to a composite endpoint including pain score at rest, pain score during movements (dynamic pain), and morphine consumption over 48 hours. Results: The treatment failed in 11 patients and was considered effective in 15 patients. Sixteen patients out of 26 had a sternal pain score ≤≤3/10 on more than 75% of observations, and the treatment was considered successful. In 23/26 patients (88%), the mean pain score at cough was ≤≤3.5/10 and the treatment was considered successful. Morphine consumption over 48 h was significantly lower in the intervention group compared to the control group 7 mg [6; 21] versus 142 mg [116; 176] (P < 0.001). Conclusions: Parasternal block with multihole catheters inserted before the surgical incision is an effective technique for postoperative analgesia and opioid reduction.